2006
DOI: 10.3748/wjg.v12.i26.4224
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic encephalopathy and Wernicke encephalopathy in association with acute pancreatitis: A clinical study

Abstract: PE occurs in early or reiteration stage of SAP, and WE in restoration stage of SAP/AP. Ocular abnormalities are the hallmarks of WE, and horizontal nystagmus is common. It is difficult to diagnose earlier an encephalopathy as PE or WE, as well as differentiate one from the other. Long fasting, hyperemesis and total parenteral nutrition (TPN) without thiamine are main causes of thiamine deficiency in the course of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 21 publications
1
46
0
1
Order By: Relevance
“…However, several reports confi rm that the onset of encephalopathy may guide the diff erential diagnosis. Pancreatic encephalopathy occurs early in the course of pancreatitis while WE presents later when vomiting or TPN use continue long enough to induce vitamin B1 defi ciency [10] . When the diagnosis is equivocal, prophylactic vitamin B1 supplementation may serve to prevent the occurrence of WE.…”
Section: Discussion ▼mentioning
confidence: 99%
“…However, several reports confi rm that the onset of encephalopathy may guide the diff erential diagnosis. Pancreatic encephalopathy occurs early in the course of pancreatitis while WE presents later when vomiting or TPN use continue long enough to induce vitamin B1 defi ciency [10] . When the diagnosis is equivocal, prophylactic vitamin B1 supplementation may serve to prevent the occurrence of WE.…”
Section: Discussion ▼mentioning
confidence: 99%
“…[2][3][4][5][6]30 Autopsy studies have showed that approximately 75% to 80% of cases in adults and 58% of cases in children have been missed by routine clinical examination. 31 Our study showed a consistent result with the literature 2-5 that most patients with nonalcoholic WE exhibited nonspecific clinical manifestations in the early stages of the disease.…”
Section: Fig 3 Mr Imaging Images Demonstrating Cortical Damage In Pamentioning
confidence: 99%
“…WE is commonly associated with prolonged alcohol abuse and is more readily diagnosed in AL patients, while WE in NA patients may be prone to misdiagnosis or a delay in diagnosis. 2,[4][5][6][7] Currently, the most effective method to confirm a diagnosis of WE in both NA and AL patients is MR imaging.…”
mentioning
confidence: 99%